Implementasi nilai Pancasila sebagai wujud identitas nasional di era digital - Aini, Najwah Nurul (Maliki Interdisciplinary Journal, 2026)
The development of technology and digital media has brought major changes to people's lives, especially in communication patterns, social behavior, and the way young people think. On one hand, the digital era provides many benefits, such as easier access to information and communication. However, on the other hand, it also creates challenges to national identity, including the spread of hoaxes, cyberbullying, decreasing nationalism, and the influence of foreign cultures without proper filtering. In this situation, the values of Pancasila have an important role as a guideline in social, national, and state life.This study aims to analyze the implementation of Pancasila values as a form of national identity in the digital era. The method used in this study is a qualitative method with a literature study approach from various sources such as scientific journals, books, articles, and other supporting data. The results of the study show that the implementation of Pancasila values in digital life can be carried out through tolerance, wise use of social media, maintaining unity, respecting other people's opinions, and improving digital literacy in society. In addition, character education and civic education also have an important role in instilling Pancasila values in the younger generation.Therefore, the implementation of Pancasila values in the digital era is an important step in maintaining Indonesia’s national identity amid globalization and technological development. Pancasila values are not only the foundation of the state, but also serve as moral guidelines for society in facing the challenges of modern digital life.